2021
DOI: 10.3390/molecules26185456
|View full text |Cite
|
Sign up to set email alerts
|

An Integrated Mutually Oriented “Chemical Profiling–Pharmaceutical Effect” Strategy for Screening Discriminating Markers of Underlying Hepatoprotective Effects to Distinguish Garden-Cultivated from Mountain-Cultivated Ginseng

Abstract: Garden-cultivated Ginseng (GG) and mountain-cultivated Ginseng (MG) both belong to Panax Ginseng C. A. Meyer. However, the effective substances which can be used to distinguish GG from MG remain obscure. Therefore, the purpose of this study was to screen for discriminating markers that can assist in the correct identification of GG and MG. HPLC Q-TOF/MS and various chemometrics methods were used to analyze the chemical profiles of 13 batches of Ginseng and to explore the characteristic constituents of both GG … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Meyer ) has been long used worldwide as a dietary supplement and/or health functional food in traditional herbal medicine. Numerous researches have also shown that this plant plays an important role in human health with beneficial properties such as antidiabetic, anticancer, anti-aging, and anti-inflammatory [ 1 , 2 , 3 ]. There are three kinds of ginseng according to cultivation methods and environmental conditions: cultivated ginseng (CG), mountain-cultivated ginseng (MCG), and mountain wild ginseng (MWG).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Meyer ) has been long used worldwide as a dietary supplement and/or health functional food in traditional herbal medicine. Numerous researches have also shown that this plant plays an important role in human health with beneficial properties such as antidiabetic, anticancer, anti-aging, and anti-inflammatory [ 1 , 2 , 3 ]. There are three kinds of ginseng according to cultivation methods and environmental conditions: cultivated ginseng (CG), mountain-cultivated ginseng (MCG), and mountain wild ginseng (MWG).…”
Section: Introductionmentioning
confidence: 99%
“…There are three kinds of ginseng according to cultivation methods and environmental conditions: cultivated ginseng (CG), mountain-cultivated ginseng (MCG), and mountain wild ginseng (MWG). MCG proliferates under natural conditions in the forest and demands a long growth period (>3 years) [ 1 , 2 , 3 , 4 ]. In general, ginseng is consumed either fresh, or as red, black, and fermented red ginseng in food and medical industries because of its many metabolite constituents [ 5 , 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%